Rumour Management in the Educational System Theoretical Perspective (Global Journal of Management and Business Research, 2014)
Rumour management in the educational system among the employees can be very debilitating for the employer as employees spend work time talking and speculating about the latest rumour Rumour is unverified information of uncertainty in which is usually by word of mouth Gossip in our educational system cannot be overemphasized Grievances are generated when employees in the educational sectors prematurely react to a rumour It cannot be completely eliminated but officials of our educational system should take prompt action by supplying the employees the fact supported by empathy rather than projection on the part of the employee Rumour are not mere chance development They arise from distinct causes If those causes can be controlled rumours will much less probably develop in our educational system Rurnour cannot be avoided among the employees as the employees are curious to know what happening in the environment they work This paper is focused on rumour management in the educational system theoretical perspective